2017
DOI: 10.1136/rmdopen-2017-000573
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic spectrum and 2-year outcome in a cohort of patients with very early arthritis

Abstract: ObjectivesTo describe the diagnostic spectrum, arthritis persistency and clinical outcomes after 2 years in patients with inflammatory arthritis (IA) of less than 16 weeks’ duration.MethodsData from the Norwegian Very Early Arthritis Clinic, a 2-year longitudinal observational study of adults with IA of ≤16 weeks’ duration, were used. Exclusion criteria were arthritis due to crystal deposits, trauma, osteoarthritis and septic arthritis. In all patients who had any follow-up information (population A), clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
(18 reference statements)
0
6
0
1
Order By: Relevance
“…Although in most EACs symptom durations <1 year are an inclusion criterion, patients with gradual symptom onset had a 1.5 higher odds ratio (OR) of developing RA than those with acute or subacute symptoms ( 10 , 25 27 ). In studies performed with patients diagnosed with very early arthritis (i.e., disease durations < 16 weeks), symptom duration did not show any relation to progression to RA ( 24 , 28 ).…”
Section: Clinical Factorsmentioning
confidence: 85%
“…Although in most EACs symptom durations <1 year are an inclusion criterion, patients with gradual symptom onset had a 1.5 higher odds ratio (OR) of developing RA than those with acute or subacute symptoms ( 10 , 25 27 ). In studies performed with patients diagnosed with very early arthritis (i.e., disease durations < 16 weeks), symptom duration did not show any relation to progression to RA ( 24 , 28 ).…”
Section: Clinical Factorsmentioning
confidence: 85%
“…Esta información es relevante en el enfoque clínico de estos sujetos y porque hace parte importante de los criterios clínicos para considerar una artralgia sospechosa de AR (22). Con respecto a las características clínicas (23,24), se evidenció que las articulaciones grandes estuvieron comprometidas con mayor frecuencia, lo que concuerda con lo publicado en estudios previos (25). El tratamiento ordenado con mayor frecuencia fueron esteroides y antirreumáticos, lo cual es congruente con lo reportado en la literatura, en la cual se ha evidenciado que el inicio temprano con fármacos antirreumáticos modificadores de la enfermedad (DMARD), asociados a esteroides como estrategia de manejo, previene el daño articular y la incapacidad funcional en pacientes con AI (26)(27)(28), lo que pudiera tener inferencia en la tasas de progresión a AR.…”
Section: Discussionunclassified
“…In terms of revision of diagnosis on follow-up, a recent two year outcome study showed that the diagnosis remained as UA in 41% patients and changed to RA in 24% of patients and after two years, arthritis resolved in 59% of EUA patients. 62 An unpublished data from Nepal shows that the diagnosis remained as UA in 57% of patients and changed to RA in 34% at 6 months follow-up. Drug free remission at six months were seen in only 4 out of 443 patients completing 6 months follow-up.…”
Section: Outcomes Of Early Undifferentiated Arthritismentioning
confidence: 98%